The path to change: key factors to the new stage of Global Information and Communication Markets - Quelho, Renata Tonicelli de Mello (Law, State and Telecommunications Review, 2010)
Peter F. Cowhey and Jonathan D. Aronson, with Donald Abelson. Transforming Global Information and Communication Markets: The Political Economy of Innovation. Cambridge: MIT Press, 2009, 341p. (R$82,62).